View Single Post
S_David
#6
Jul15-09, 10:49 AM
P: 601
I have the same problem again in the following code:

gA = 10;
M = 1;
Ne = 1;
If[M >= 1, m = M, m = 0];
For[SNRdB = 0, SNRdB <= 10, SNRdB++,
 SNR = 10^(SNRdB/10);
 Print[F1 = \!\(
\*UnderoverscriptBox[\(\[Sum]\), \(r = m\), \(M\)]\(
\*UnderoverscriptBox[\(\[Sum]\), \(i = 0\), \(M - r\)]\(
\*UnderoverscriptBox[\(\[Sum]\), \(j = 0\), \(r + i\)]\(
\*UnderoverscriptBox[\(\[Sum]\), \(k = 0\), \(j*\((Ne - 1)\)\)]
\*SuperscriptBox[\((\(-1\))\), \(i + j\)]*Binomial[M, r]*
        Binomial[M - r, i]*Binomial[r + i, j]*
\*SuperscriptBox[\(E\), 
FractionBox[\(\(-j\)*SNR\), \(gA\)]]*
\*SuperscriptBox[\((
\*FractionBox[\(SNR\), \(g\)])\), \(k\)]\)\)\)\)]]
For[SNRdB = 0, SNRdB <= 10, SNRdB++,
 SNR = 10^(SNRdB/10);
 Print[F2 = 1 - \!\(
\*UnderoverscriptBox[\(\[Sum]\), \(r1 = m\), \(M - 1\)]\(
\*UnderoverscriptBox[\(\[Sum]\), \(i1 = 1\), \(M - r1\)]\(
\*UnderoverscriptBox[\(\[Sum]\), \(j1 = 1\), \(r1 + i1\)]\(
\*UnderoverscriptBox[\(\[Sum]\), \(k1 = 0\), \(j1*\((Ne - 1)\)\)]
\*SuperscriptBox[\((\(-1\))\), \(i1 + j1\)]*Binomial[M, r1]*
         Binomial[M - r1, i1]*Binomial[r1 + i1, j1]*
\*SuperscriptBox[\(E\), 
FractionBox[\(\(-j1\)*SNR\), \(gA\)]]*
\*SuperscriptBox[\((
\*FractionBox[\(SNR\), \(g\)])\), \(k1\)]\)\)\)\)]]

1-1/\[ExponentialE]^(1/10)

1-\[ExponentialE]^-1/10^(9/10)

1-\[ExponentialE]^-1/10^(4/5)

1-\[ExponentialE]^-1/10^(7/10)

1-\[ExponentialE]^-1/10^(3/5)

1-\[ExponentialE]^-1/Sqrt[10]

1-\[ExponentialE]^-1/10^(2/5)

1-\[ExponentialE]^-1/10^(3/10)

1-\[ExponentialE]^-1/10^(1/5)

1-\[ExponentialE]^-1/10^(1/10)

1-1/\[ExponentialE]

1

1

1

1

1

1

1

1

1

1

1
Why is the second part constant, even though it is a dependent on SNR?

Regards